A to Z Drug facts - Tatro, David S. ;Borgsdorf, Larry R. (St. Louis, Missouri : Facts and Comparisons, 2006)
"From the leading provider of drug information, A to Z Drug Facts is an easy-to-use, alphabetically organized drug information reference, integrating successful drug therapy protocols with patient care considerations." "The 7th edition contains more than 4,700 products, including the newest FDA approvals, and the latest indications, dosages, side effects, and patient information."--Jacket
Drug monographs A to Z -- FDA pregnancy categories -- General management of acute overdosage -- Management of acute hypersensitivity reactions -- Calculations -- International system of units -- Normal laboratory values -- Drug names that look and sound alike -- Oral dosage forms that should not be crushed or chewed -- Childhood immunization schedule
Includes index.
Keywords: CHEMOTHERAPY